2008
DOI: 10.1183/09031936.00133907
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and polygraphic evolution of sleep-related breathing disorders in adolescents

Abstract: It has been suggested that sleep-related breathing disorders (SRBD) involve a continuum that develops over the course of life. If modifiable factors could be identified, the progression of SRBD could perhaps be addressed early in life. Although some studies have looked at the evolution of SRBD in pre-pubertal children, very few studies obtained data in adolescents.Anthropometric, clinical and polygraphic variables were collected during a 4-yr follow-up study among 148 normal adolescents after initial cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Adolescents is crucial in the development of SRBD because hormone changes during this period. Sánchez-Armengol and colleagues conducted a 4-year follow-up study and demonstrated that habitual snoring tended to persist during adolescents if no intervention was undertaken [26]. In the present study, we found overweight, residence, birth history and parental education level were correlated with snoring and SRBD in adolescents.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Adolescents is crucial in the development of SRBD because hormone changes during this period. Sánchez-Armengol and colleagues conducted a 4-year follow-up study and demonstrated that habitual snoring tended to persist during adolescents if no intervention was undertaken [26]. In the present study, we found overweight, residence, birth history and parental education level were correlated with snoring and SRBD in adolescents.…”
Section: Discussionsupporting
confidence: 55%
“…In weighty populations, breathing is not smooth during sleep, which may result in sleep apnea [19]. Sánchez-Armengol et al indicated that healthcare interventions might have a beneficial effect on snoring by avoiding weight gain in adolescents [26]. …”
Section: Discussionmentioning
confidence: 99%
“…4 Children with enlarged tonsils and adenoids may have increased upper airway collapsibility. 5 Several studies suggest that SDB may be more frequent in children of African-American race compared with Caucasians 6,7 and that boys may be at higher risk of SDB than girls, [8][9][10] especially in studies that included teenagers, 11 where pubertal hormonal changes likely contribute to the gender differences observed in adults. In addition, children with craniofacial anomalies and those with disorders affecting upper airway patency are at higher risk of SDB.…”
Section: Prevalence and Risk Factorsmentioning
confidence: 98%
“…A 4‐year follow‐up study by Sánchez‐Armengol et al . demonstrated that SDB in 148 adolescents at both baseline (14.3‐years old) and follow‐up (18.5‐years old) was associated with higher BMI and central fat distribution , although the authors were not able to examine trajectories of SDB across different developmental stages (i.e. from childhood to adolescence) due to the age of the sample.…”
Section: Introductionmentioning
confidence: 99%